The Relationship between Social Capital, Human Capital, and the Level of Welfare of Farmers in Ponorogo, Indonesia - Achmad Tjachja Nugraha; Fikriyah Fikriyah; Izatul Ihsansi Hidayana; Salsa Alifia Najid; Gunawan Prayitno (Khazanah Sosial, 2023)
Community empowerment is one of the solutions to overcome the problem of poverty in an area. Community empowerment can be carried out by utilizing local potential and developing aspects and social capital. Based on the theory of the poverty circle, several factors cause poverty, including income levels, education levels, and the amount of consumption. Ponorogo Regency is one of the top 10 food support districts in East Java, with progress in the agricultural sector capable of supporting regional food security. However, many underprivileged residents have a poverty rate 2022 of 9.32% of the total population. Based on these facts, this study aims to reveal the relationship between social capital, education level, and income level in Ponorogo Regency. This study uses multiple linear regression analysis with independent variables (Xn), including the level of public education (X1) and human capital (X2), as well as the dependent variable (Y), namely the level of welfare of the people of Ponorogo Regency. The analysis results show that in Ponorogo Regency, there is a correlation between social capital and the level of education and community welfare. The level of social welfare is influenced by education and human capital. The higher the education level and human capital, the higher the social welfare and social capital formed. The development of social capital in networks at the educational level of Ponorogo Regency is very closely related, especially to participation in the religious field. Likewise, the relationship with norms on social capital in which the community has no tendency for a certain level of education related to the desire to implement applicable norms. However, participation in traditional activities has a closer relationship only at the elementary to secondary education level. The analysis results also show that the people of Ponorogo Regency with any income level have a close relationship with all elements of social capital, namely trust, social networks, and norms. Low-income people are associated with an increase in social class.